Educomunicação: uma proposta para o Ensino de Ciências - Stein, Suleima Tello (2011)
Science education in Brazil has long been distant and disconnected from the reality of the students. There is no relationship between what is learned in class and how that content is put in context. The content is taught mostly through books, and many times, only through expositive methods, leaving instruction highly unnapealing to the students. As communication and information technology develops and improves, there is a growing need for it to be used inside the classroom. However, schools face several obstacles, including a lack of qualifiedteachers. Students are ready and excited to use and learn with new methods and technologies, but the teachers are not prepared or qualified to use them. The educommunication seems to be the way to solve this dichotomy, as it allows students to participate more actively, helping teachers, and creating a more reflexive approach to education. The research presented here shows education through the use of educommunication in Science, in an experiment using a school radio system. The goal is to analize the use of a radio system in the teaching and learning process for Science, as well as how its use can contribute to and enable a more reflexive approach with communication tools used in the classroom. Research qualitative and quantitative, character has the current of thought dialectical materialism assumes that the interpretation of reality based on contradictions a word view and praxis. This paper’s research took place in a school in Manaus (Amazonas, Brazil), and included observation, questionnaire uses (Likert scale), and an experiment involving ‘airing’ Science educational programs on a school radio system.